Neurological Manifestations of Sanjad–Sakati Syndrome: New Three Reported Cases from Tunisia - Bouattour, Nadia; KamounFeki, Fatma; Bouchaala, Wafa; Ben Nsir, Siham; Triki, Chahnez (Journal of Pediatric Neurology, 2020)
Sanjad–Sakati syndrome (SSS), or hypoparathyroidism–mental retardation dysmorphism syndrome, is a rare autosomal recessive congenital disorder characterized by congenital hypoparathyroidism, growth and neurodevelopmental delay, acute symptomatic seizures due to hypocalcemia, and dysmorphic features. The syndrome is underdiagnosed, and neurological manifestations are not previously described. We report three Tunisian patients with SSS revealed by acute symptomatic hypocalcemic epileptic seizures. Despite the well-controlled seizures, patients tend to continue having poor growth and neurological outcome. The diagnosis of SSS allowed for proper treatment of the patients, prevented associated comorbidities, and provided genetic counseling to their families.
Keywords: Sanjad–Sakati Syndrome; hypocalcemia; acute symptomatic seizures